The investigation of airway management capacity of v-gel and cobra-PLA in anaesthetised rabbits - Uzun,Metehan (2015)
PURPOSE:To evaluate the applicability and airway management capacity of v-gel(r) and Cobra PLA in rabbit anaesthesia during assisted (AV) or controlled ventilation (CV).METHODS:This study was carried out in 44 adult New Zealand white rabbit. Baseline arterial pH, PaCO2 and PaO2 values were recorded. Anaesthesia was induced with 5 mg/kg xylasine and 35 mg/kg ketamine HCI combination. AV rabbits were assigned as; control (CG-AV; n=5), LMA (LMA-AV; n=5), cobra PLA (PLA-AV; n=5) and v-gel (v-gelAV; n=5). Rabbits have CV were also assigned as; ET (ET-CV; n=6), LMA (LMA-CV; n=6), cobraPLA (PLA-CV; n=6) and v-gel (v-gelCV; n=6). All measurements were repeated 1st, 5th, 15th and 30th mins during anaesthesia.RESULTS: The less insertion time, number of attempt and complications are recorded in v-gel applied rabbits compared to other apparatus. For arterial pH values significant differences are recorded in especially at 15th and 30th min between groups of CV (p<0.005 or p<0.001). All groups had similar results with each other during anaesthesia for PaCO2 except for LMA-CV group.CONCLUSION:The v-gel may be used as airway device in rabbit anaesthesia undergoing AV or CV and also can be a suitable alternative to endotracheal tubes and laryngeal mask airway.